Democracy in captivity: prisoners, patients, and the limits of self-government - Berk, Christopher D. (University of California Press, 2023)
"Past and present efforts to reform prisons and mental hospitals are haunted by a desire to democratize custody. Embedded in this desire, Democracy in Captivity shows, is a persistent anxiety about who ought to govern ward life. Stuck in the middle of the social engineering efforts of both custodians and would-be democratic reformers are prisoners and patients themselves. Wards struggle for representation and, invariably, provoke backlash -- not only in the blunt forms of restraint chairs, riot gear, and a surgeon's scalpel, but also more covert sorts of maneuvering under the cover of 'democratic' management. Christopher D. Berk explains how these more subtle moves facilitate exploitation, entrench disenfranchisement, and naturalize authoritarian rule. In doing so, he uses custody as a lens to examine wider pathologies that have captured the politics of punishment today"--